Camel Production and Management Systems in Different Agro-ecological Zones of Rajasthan - Bhakat, Champak; Chaturvedi, D; Sahani, M S (Annals of Arid Zone, 2016)
Â A study was conducted on various aspects of camel production and management systems in two agro-ecological zones of Bikaner and PalL In a camel herd average representation of I to 4 year age group of camels was found to be less at Pali as compared to Bikaner district. The above 4-yearcage group female camels formed maximum percentage in a herd of both the regions. Bikaner region was dominated by camel user (79.33%), where as in Pali district camel breeders formed the major group (65.33%). The main purpose of camel rearing was carting in Bikaner and trading in Pali district. The purpose of camel rearing significantly (P<O.OI) varied between two agro-ecological zones of Bikaner and PalL In both regions camel keeper having single camel were maximum in irrigated belt as compared to un-irrigated area and farmers having more than 5 camels were more in un-irrigated region than irrigated belt. In both the regions farmers having single camel were rearing camel in intensive system. The farmers having 2-5 camels used to send th<:ir camel for grazing around village (upto 50 km range). Majority of farmers owning 5 camels, reared their camel by sending them in migration with some herds men. Chi-square test indicated that camel keeping pattern significantly (P<O.OI) influenced the rearing practices and feeding management system of these areas. In Bikaner region seasonal migration was more (84.75%), where as in Pali region prolonged migration was found to be maximum (79.32%). In both type of migration short distance (upto 50 km) covered was more in Bikaner region where as long distance covered (50 km) was more in Pali area. In both regions camel rearing was found to be 3rd source of revenue, rearing livestock’s other than camel like cattle, sheep and goat were 2nd ways, whereas agriculture was the first source of revenue of farmers. Key words: Camel, management, agro-ecology, production and economics.